2020
DOI: 10.1371/journal.pone.0242917
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and serologic response in SARS-CoV-2 induced ARDS: A cohort study

Abstract: Background The viral load and tissue distribution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remain important questions. The current study investigated SARS-CoV-2 viral load, biodistribution and anti-SARS-CoV-2 antibody formation in patients suffering from severe corona virus disease 2019 (COVID-19) induced acute respiratory distress syndrome (ARDS). Methods This is a retrospective single-center study in 23 patients with COVID-19-induced ARDS. Data were collected within routine intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…NAbs are antibodies that can directly interfere with virus’ replication and prevent virus from entering target cells. In SARS-CoV-2 specific-NAbs, IgG and IgM are the predominant antibody followed by the IgA ( Rojas et al., 2020 ; Schlesinger et al., 2020 ). Neutralizing antibody titers were in accordance with anti-SARS-CoV-2 IgG and IgM antibody titers ( Figueiredo-Campos et al., 2020 ; To et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…NAbs are antibodies that can directly interfere with virus’ replication and prevent virus from entering target cells. In SARS-CoV-2 specific-NAbs, IgG and IgM are the predominant antibody followed by the IgA ( Rojas et al., 2020 ; Schlesinger et al., 2020 ). Neutralizing antibody titers were in accordance with anti-SARS-CoV-2 IgG and IgM antibody titers ( Figueiredo-Campos et al., 2020 ; To et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al [ 229 ] demonstrated that, in severe COVID-19 patients coinfected with S. pneumoniae, Haemophilus parainfluenzae or Neisseria meningitides , the numbers of SARS-CoV-2 virions were significantly lower than in uncomplicated SARS-CoV-2 infections. Similarly, Schlesinger et al [ 230 ] reported that, among COVID-19 patients admitted to the intensive care unit, “No difference of viral load was found in tracheal or blood samples with regard to 30-day survival or disease severity. SARS-CoV-2 was never found in dialysate.…”
Section: Discussionmentioning
confidence: 99%
“…With clinical COVID-19, there have been a number of publications on viral RNA in the blood with the first publication using data from the early 2020 Wuhan outbreak. 81,82 Since then, more extensive publications from Spain, 83,84 Germany, 85,86 United States [87][88][89] and Norway 90 have been published using outpatients, hospital ward patients and critically ill patients. The positive detection rate is between 28% and 32% of hospitalized patients; however, those in intensive care have rates up to 78%.…”
Section: Dissemination and Transmission Viraemiamentioning
confidence: 99%